Fostering Well-being in Social Interaction: A Systematic Review of the Application of Positive Psychology in Sociolinguistics Pedagogy - Samtidar; Safar Nur, Muhammad; Muhammad Irawan, Andi (Har Press Indonesia, 2025)
Research in second language acquisition (SLA) has undergone a significant affective turn over the last decade, with a burgeoning interest in the role of positive emotions in the learning process. In line with this shift, Positive Psychology (PP), as the scientific study of human well-being and flourishing, has emerged as a promising framework for enhancing language learner motivation, engagement, and performance. However, while research on the application of PP in SLA generally has grown rapidly, its application within the nuanced and socially embedded domain of Sociolinguistics pedagogy remains critically underexplored. This systematic review aims to bridge that gap by synthesizing the relevant literature from 2015 to 2025. It proposes a theoretical framework for integrating PP principles into sociolinguistic pedagogy. The central argument is that the core concepts of PP, particularly Seligman's PERMA model (Positive Emotion, Engagement, Relationships, Meaning, and Accomplishment), offer a powerful analytical lens not only for enhancing communicative and intercultural competence but also for actively fostering positive language attitudes and creating inclusive, supportive classroom environments. By mapping the conceptual synergy between PP's goal of promoting well-being and sociolinguistics' goal of understanding language in social context, this review articulates a transformative pedagogy. This pedagogy moves beyond the critical analysis of linguistic phenomena toward the active cultivation of the psychological strengths necessary for students to navigate and positively contribute to a linguistically diverse world. The review concludes by outlining a detailed future research agenda to empirically validate the proposed synthesis and to spur the development of a more humanistic and empowering sociolinguistic pedagogy.